International Consensus Statement on Allergy and Rhinology: Allergic Rhinitis. Issue 2 (13th February 2018) - Wise, Sarah K.; Lin, Sandra Y.; Toskala, Elina; Orlandi, Richard R.; Akdis, Cezmi A.; Alt, Jeremiah A.; Azar, Antoine; Baroody, Fuad M.; Bachert, Claus; Canonica, G. Walter; Chacko, Thomas; Cingi, Cemal; et al.
Abstract : Background: Critical examination of the quality and validity of available allergic rhinitis (AR) literature is necessary to improve understanding and to appropriately translate this knowledge to clinical care of the AR patient. To evaluate the existing AR literature, international multidisciplinary experts with an interest in AR have produced the International Consensus statement on Allergy and Rhinology: Allergic Rhinitis (ICAR:AR). Methods: Using previously described methodology, specific topics were developed relating to AR. Each topic was assigned a literature review, evidence‐based review (EBR), or evidence‐based review with recommendations (EBRR) format as dictated by available evidence and purpose within the ICAR:AR document. Following iterative reviews of each topic, the ICAR:AR document was synthesized and reviewed by all authors for consensus. Results: The ICAR:AR document addresses over 100 individual topics related to AR, including diagnosis, pathophysiology, epidemiology, disease burden, risk factors for the development of AR, allergy testing modalities, treatment, and other conditions/comorbidities associated with AR. Conclusion: This critical review of the AR literature has identified several strengths; providers can be confident that treatment decisions are supported by rigorous studies. However, there are also substantial gaps in the AR literature. These knowledge gaps should be viewed as opportunities for improvement, as often the things that we teach and the medicine that we practice are not based on the best quality evidence. This document aims to highlight the strengths and weaknesses of the AR literature to identify areas for future AR research and improved understanding.